1991
DOI: 10.1177/002224379102800305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Price, Brand, and Store Information on Buyers’ Product Evaluations

Abstract: The authors report a study of the effects of price, brand, and store information on buyers’ perceptions of product quality and value, as well as their willingness to buy. Hypotheses are derived from a conceptual model positing the effects of extrinsic cues (price, brand name, and store name) on buyers’ perceptions and purchase intentions. Moreover, the design of the experiment allows additional analyses on the relative differential effects of price, brand name, and store name on the three dependent variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
2,161
8
108

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,967 publications
(2,332 citation statements)
references
References 10 publications
55
2,161
8
108
Order By: Relevance
“…These subjective perceived prices can be both an indicator of the amount of sacrifice associated with the purchase of a product as well as an indicator of product quality (Monroe and Krishnan 1985). Consumer perception of monetary value of goods or services is a result of a mental accounting process of their perceptions of quality and sacrifice (Dodds et al 1991;Suri et al 2003). The perceived monetary value is positive when perceptions of quality are greater than perceptions of sacrifice (Monroe 1990).…”
Section: Perceived Monetary Valuementioning
confidence: 99%
See 2 more Smart Citations
“…These subjective perceived prices can be both an indicator of the amount of sacrifice associated with the purchase of a product as well as an indicator of product quality (Monroe and Krishnan 1985). Consumer perception of monetary value of goods or services is a result of a mental accounting process of their perceptions of quality and sacrifice (Dodds et al 1991;Suri et al 2003). The perceived monetary value is positive when perceptions of quality are greater than perceptions of sacrifice (Monroe 1990).…”
Section: Perceived Monetary Valuementioning
confidence: 99%
“…The perceived monetary value is positive when perceptions of quality are greater than perceptions of sacrifice (Monroe 1990). In turn, this perceived monetary value affects consumers' intention to use a product (Cronin et al 2000;Dodds et al 1991;Zeithaml 1988). In the continued usage context, such a mental accounting process for the perception of monetary value can be clearer through the direct experience with the services/products.…”
Section: Perceived Monetary Valuementioning
confidence: 99%
See 1 more Smart Citation
“…In the consumer products area, prior studies have investigated framing effects on consumer perception and purchase intention [9,12,41,43,56]. Purchase intention describes the likelihood of a customer purchasing a product [22,26,37]. Fishbein and Ajzen [26, p 288] defined behavioral intention as the tendency to want to take a specific action.…”
Section: Framing Effect and Purchase Intentionmentioning
confidence: 99%
“…Based upon previous empirical studies, which mostly state that there is exists a linkage between value, intentions, and satisfaction, the results showed that value was found to have a strong and significant impact on satisfaction; and satisfaction in turn has a significant effect on intentions. Previous studies have provided ample evidence for the positive influence that perceived value has on purchase intention or consumers' willingness to buy (Dodds et al 1991;Monroe 1990;Zeithaml 1998).…”
Section: Customer-perceived Valuementioning
confidence: 99%